A comparison of maxillofacial growth in Chinese children with isolated cleft palate treated with two different palatoplasty techniques without relaxing incisions: a preliminary study - Sadam Ahmed Elayah; Jiayi Yin; Waseem Saleh Al-Gumaei; Hamza Younis; Karim Ahmed Sakran; Ziwei Tang; Mubarak Ahmed Mashrah; Grace Paka Lubamba; Min Wu; Yang Li; Bing Shi (BMC, 2023)
Abstract Objective To assess the maxillofacial growth of patients with isolated cleft palate following the Sommerlad-Furlow modified technique and compare it with the effect of the Sommerlad technique. Study design A Retrospective Cohort Study. Methods A total of 90 participants, 60 patients with non-syndromic isolated soft and hard cleft palate (ISHCP) underwent primary palatoplasty without relaxing incision (30 patients received the Sommerlad-Furlow modified (S-F) technique and 30 received Sommerlad (S) technique). While the other 30 were healthy noncleft participants with skeletal class I pattern (C group). All participants had lateral cephalometric radiographs at least 5 years old age. All the study variables were measured by using stable landmarks, including 11 linear and 9 angular variants. Results The means age at collection of cephalograms were 6.03 ± 0.80 (5-7 yrs) in the S group, 5.96 ± 0.76 (5-7 yrs) in the S-F group, and 5.91 ± 0.87 (5-7 yrs) in the C group. Regarding cranial base, the results showed that there were no statistically significant differences between the three groups in S-N and S-N-Ba. The S group had a significantly shortest S-Ba than the S-F & C groups (P = 0.01), but there was no statistically significant difference between S-F and C groups (P = 0.80). Regarding skeletal maxillary growth, the S group had significantly shorter Co-A, S- PM and significantly less SNA angle than the C group (P =  < 0.01). While there was no significant difference between S-F & C groups (P = 0.42). The S group had significantly more MP-SN inclination than the C group (P =  < 0.01). Regarding skeletal mandibular growth, there were no statistically significant differences in all linear and angular mandibular measurements between the three groups, except Co-Gn of the S group had a significantly shorter length than the C group (P = 0.05). Regarding intermaxillary relation, the S-F group had no significant differences in Co-Gn-Co-A and ANB as compared with the C group. The S group had significantly less ANB angle than S-F & C groups (P = 0.01 & P =  < 0.01). In addition, there were no significant differences in all angular occlusal measurements between the three groups. Conclusion As a preliminary report, Sommerlad-Furlow modified technique showed that maxillary positioning in the face tended to be better, and the intermaxillary relationship was more satisfactory than that in Sommerlad technique when compared them in healthy noncleft participants.